Tingkat Kesukaan Panelis Terhadap Teh Kombucha Dengan Menambahkan Apel Hijau Malang Dan Bit Merah Melalui Uji Organoleptik - Pande Made Utari Mahadewi; Ni Luh Suastuti; Lidjah Magdalena Massenga (JURNAL GASTRONOMI INDONESIA, 2022)
Kombucha tea is a traditional drink fermented from a solution of tea and sugar using a kombucha microbial starter called SCOBY (Symbiotic Culture of Bactery and Yeast), which contains bacteria and yeast (acetobacter xylinum, several types of yeast, such as Saccharomyces cerevisiae) which is fermented for 14 days in room temperature. Tea blend with Malang Green Aplle and beetroot will give a new creation of tea that we can get red color tea and we also get the healty benefit from apple and beetroot.  This study aims to determine the preference level of 15 panelists through organoleptic test. The assessment indicators in this study are sweetness, acidity, bitterness, aroma and colour. The results of organoleptic tests on kombucha tea blend with Malang green apples and beetroot are: sweetness, acidity,  and color of this Kombucha blend are really liked and aroma get like level, and bitterness get kinda like, but overall panelist give really like the blend Kombucha with green aplle malang and beetroot.It can be said that kombucha blend with green apple Malang and Beetroot have a very good sweetness, acidity aroma and also interesting color.